PENDEKATAN DIAGNOSIS DAN TATA LAKSANA MULTIDISIPLIN JANGKA PANJANG PADA NEUROPATI HEREDITER CHARCOT MARIE TOOTH - Putri Widya Andini,* Manfaluthy Hakim,* Fitri Octaviana,* Luh Ari Indrawati,* Winnugroho Wiratman,* (Neurona Majalah Kedokteran Neuro Sains, 2020)
NEUROPATHY IS THE MOST COMMON INHERITED NEUROMUSCULAR DISEASES WITH CHARCOT MARIE TOOTH BEING THE MOST COMMON FORM IT IS CHARACTERISED BY DEGENERATION OF PERIPHERAL SENSORY AND MOTOR NERVES DUE TO AXONAL DEGENERATION OR DEMYELINATION